Design, analysis and fabrication of mini taffy / Amiratul Aqilah Mohd Zainol and Suhadiyana Hanapi - Mohd Zainol, Amiratul Aqilah; Hanapi, Suhadiyana (School of Mechanical Engineering, 2022)
The Mini Taffy Puller Machine is an innovation inspired by the existing Taffy Puller Machine. Currently, people are staying at home due to the pandemic. Thus, they are constantly bored and some of them have lost their jobs. So, with this machine, it will benefit some people to start a small business or fill their free time by making candy. This device is designed with innovations that are user friendly, it is easy to understand, and safe to handle so it will be safe for children to use too. Plus, the device is lightweight and easy to carry. From the survey that has been conducted using Google Form, most respondents agree that this device will help people start a small business, hobby enthusiasts, and help people with hypoglycemia as we can choose our own ingredients, flavour, colour, and level of the sweetness. By fabricating this device, it will bring a huge impact on taffy making since it will improve the process of making the taffy itself